2021
DOI: 10.1002/solr.202100207
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Optoelectronic Phenomena for a Semitransparent Nonfullerene Photovoltaic System

Abstract: A unique feature of nonfullerene acceptors (NFAs) is their strong photoabsorption capability at longer wavelengths and electrostatic potentials (ESPs), which is expected to increase the photocurrent density (J) for bulk heterojunction (BHJ)‐based semitransparent organic solar cells (ST‐OSCs). Indeed, the interior spin‐optoelectronic phenomena are incredibly rich, and it remains challenging to correlate them with a complete photovoltaic process. Here, a prototypical PTB7‐Th: IEICO‐4F‐based ST‐OSC, with an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previously, a mean value of B hf <2 mT was also found in the PTB7‐Th:IEICO‐4F system. [ 19 ] The reduction of the B hf implies that the ISC and RISC events have less probability to happen for the nonfullerene BHJ systems.…”
Section: Theoretical Models and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, a mean value of B hf <2 mT was also found in the PTB7‐Th:IEICO‐4F system. [ 19 ] The reduction of the B hf implies that the ISC and RISC events have less probability to happen for the nonfullerene BHJ systems.…”
Section: Theoretical Models and Discussionmentioning
confidence: 99%
“…Previously, a mean value of B hf <2 mT was also found in the PTB7-Th:IEICO-4F system. [19] The reduction of the B hf implies that the ISC and RISC events have less probability to happen for the nonfullerene BHJ systems. Based on our experimental results and the theoretical analyses, the PM6:Y6 organic BHJ system has the smallest Δg and B hf.…”
Section: S T0mentioning
confidence: 99%
See 2 more Smart Citations
“…Nonfullerene acceptor (NFA)-based organic bulk heterojunction (BHJ) solar cells have boosted the photovoltaic power conversion efficiencies (PCEs) to a completely new height. They are synthesized to be practically useful for future highly efficient, large-scale, semitransparent, and flexible organic solar cells (OSCs). In competition to the historically well-established fullerene system, the NFAs contain desirable optoelectronic characteristics in terms of feasibly tailored molecular structures, extensive photo-absorption strengths at near infrared regions, and balanced charge-carrier transports. , It has been demonstrated that the dissociation of photogenerated species is firmly linked with the electronic spin property. , As a matter of fact, magnitudes of short-circuit current densities ( J sc ) are spin-dependent . In addition, the energy loss due to the polaron back transfer (PBT) from interfacial charge-transfer states (CTSs) to triplet exciton (TE) states is known to be spin-related .…”
Section: Introductionmentioning
confidence: 99%